ANÁLISIS DE LA CALIDAD DEL SERVICIO QUE PRESTA, LA AGENCIA DE VIAJE ABAD CASTILLO TRAVEL CIA.LTDA, EN LA CIUDAD DE LOJA - Villavicencio Castillo, Jorge Enrique (2019)
The current investigation was carried out at the Abad Castillo Travel Cia Ltda. Travel Agency located in the city of Loja in the parish of the low pedestal sector, on José Antonio Eguiguren and Lauro Guerrero streets. The importance of quality has been transcending since the archaic times, from the Hammurabi code that talks about the quality of houses, and with the evolution of the industry began to produce mass products which implies greater quality control in the services, making the study of the current company on the service and products offered to its users relevant. The general objective of the current study is "Analyze the quality of the service provided by the travel agency," ABAD CASTILLO TRAVEL CIA.LTDA, IN THE CITY OF LOJA ". For this, three specific objectives were raised: The main one was to diagnose the current situation of the travel agency Abad Castillo Travel CIA, LTDA. Data collection was started using the situational matrix and interviews, applying if the descriptive, inductive, analytical method to differentiate the elements of the problem that is in the company, and the use of direct observation technique, helped corroborate data obtained, while the inductive method allowed to analyze the investigated facts and clarify the important facts. For the second objective that consists in “Evaluating the quality of the service offered by the Abad Castillo Travel Agency CIA, LTDA”. The surveys were carried out based on the servqual methodology (it groups five dimensions to measure the quality of the service), obtaining statistical data, from the surveys carried out on 100 clients of the company. In the analysis and interpretation of the results of the surveys, the methods were applied: analytical, descriptive, qualitative and quantitative that helped the process of verifying results and knowing the important facts of the survey. For the realization of the third objective is based on "Propose strategies for improving the quality of service provided by the travel agency Abad Castillo Travel CIA, LTDA". the results obtained from the previous objectives were located, in the SWOT matrix, and in fact, internal and external factors of the company are obtained, giving if the approach of strategies to be developed. According to the results obtained in each of the dimensions investigated, it is concluded that the Travel Agency is well aimed at offering a quality service, but should improve in the dimensions of: responsiveness, security, empathy, tangible elements where it was found a deficit in some questions that are with low ratings and in terms of the quality of the services offered to customers, there are strategies for improving the service and product that is going to be offered to its customers and users. - 5 - Establishing, as well as the primary direction to the company to take into account the proposed strategies, the same as with its implementation will strengthen the business and tourism environment, which must necessarily meet all companies that decide to offer a tourist service or product. Allowing a correct functionality in the attention and service to users and does not generate discomfort in future or existing customers, agreeing to be recognized as a quality tourism services company. service times should be improved with the documentation and information of the products they offer and procedures they request, allowing to have a correct functionality in the service and not generate discomfort in customers fixed and new allowing to be recognized as a quality services company.